(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The aim of the research is to verify the effectiveness of educational electronic games in developing some health skills among a sample of autistic children in Lattakia Governorate, their ages ranged between (5-6) years, and the research sample amounted to (12) autistic children, which were divided into an experimental group consisting of (8) children and a control group consisting of (8) children. To achieve this goal, the researcher used the quasi-experimental method. The children of the experimental group were subjected to a set of educational electronic games in order to develop their health skills. The results showed that there were statistically significant differences between the average scores of the children of the experimental group and the average scores of the children of the control group on the health skills test after the application of educational electronic games, in favor of the children of the experimental group, and there were statistically significant differences between the average scores of the children of the experimental group on the health skills test in the two tribal applications. and dimensional, in favor of dimensional application. The results of the study also showed that there were no statistically significant differences between the average scores of the experimental group children in the post application and their average scores in the delayed application on the health skills test. In light of the results, the researcher recommended conducting studies on the use of educational electronic games in developing different types of concepts and skills for autistic children, and conducting other studies on preparing programs for autistic children to develop different skills for them.